FISCAL STIMULATION OF SPATIAL DEVELOPMENT: THE EU COUNTRIES’ CASES - V. Khudolei; M. Bespalov; S. Tulchynska; R. Tulchinsky; N. Kholiavko (Фінансово-кредитна діяльність: проблеми теорії та практики)
The objective of this article is to form the basis for strengthening the fiscal stimulus spatial development of regional economic systems in the context of decentralization. The methods of research: dialectical, synthesis, analysis, generalizations and monographic, abstraction and generalizations. Results. The authors consider the «fiscal space» as a certain economic spatial formation, formed by elements of the regional economic system, which are involved in the construction of budget components and management of financial flows. The positive impact of the fiscal policy’s implementation in the context of decentralization is highlighted, as well as a certain imbalance of certain areas that provoke the search for ways of fiscal policy objectives intra-regional coordination. Summarizing the experience of European countries on fiscal stimulation of the development of regional economic systems, the following trends are highlighted: first, the main regulatory instruments are tax and budgetary policies, the level of their development and independence in the regions of countries; secondly, regional fiscal policy is always subordinated to the national economic development strategy; thirdly, taxes are becoming a tool for both stimulating and restraining the regions’ development. The article proposes the ways to smooth out negative challenges and the task of regional development’s fiscal stimulation is defined. The experience of European countries allows us to explore the prospects for developing tools for fiscal stimulus to ensure the sustainability and modernization of the regional space. Conclusions. The experience of European countries in the implementation of fiscal policy in the context of decentralization and the functioning of local self-government is studied. Despite the binding nature and dominance of European norms in fiscal policy, each country has formed its own strategic goals in economic development. This allowed preserving the national identity of individual territories, the specificity of the cultural value’s impact on the fiscal stimulation of regional economic systems. The authors come to the conclusion that the adaptation of the best practices in European countries in the Ukrainian economy’s conditions requires their reformatting under the goals and strategies of national economic policy. Directions of implementation of EU countries’ experience in fiscal stimulus of regional space in Ukraine are identified in the article.